Inhibition of ACSL4 attenuates ferroptotic damage after pulmonary ischemia‐reperfusion. Issue 12 (18th October 2020) - Xu, Yixin; Li, Xuehan; Cheng, Yan; Yang, Mingan; Wang, Rurong
Abstract: Lung ischemia‐reperfusion (IR) injury is a common clinical pathology associated with high mortality. Ferroptosis, a novel mode of cell death elicited by iron‐dependent phospholipid peroxidation, has been implicated in ischemic events. Acyl‐CoA synthetase long‐chain family member 4 (ACSL4) is one of the main enzymes in pro‐ferroptotic lipid metabolism. In this study, the involvement of ferroptotic death in different durations of reperfusion was evaluated by assessing the iron content, malondialdehyde, and glutathione levels, ferroptosis‐related protein expression, and mitochondria morphology. The roles of ferroptosis‐specific inhibitor, liproxastin‐1 (Lip‐1), and ACSL4 modulation in a preventive regimen were assessed in vivo and in vitro. The hallmarks of pulmonary function, such as histological lung injury score, wet/dry ratio, and oxygenation index, were evaluated as well. Results showed that lung IR increased the tissue iron content and lipid peroxidation accumulation, along with key protein (GPX4 and ACSL4) expression alteration during reperfusion. Pretreatment with Lip‐1 inhibited ferroptosis and ameliorated lung IR‐induced injury in animal and cell models. In addition, administering ACSL4 inhibitor rosiglitazone before ischemia diminished the ferroptotic damage in IR‐injured lung tissue, consistent with the protective effect of ACSL4 knockdown on lung epithelial cells subjected to hypoxia/reoxygenation. Thus, this study delineated that IR‐induced ferroptotic cell death in lung tissue and ACSL4 were correlated with this process. Inhibition of ferroptosis and ACSL4 mitigated the ferroptotic damage in IR‐induced lung injury by reducing lipid peroxidation and increasing the glutathione and GPX4 levels.